Numerical simulation of laminar non-Newtonian blood flow under varying Reynolds numbers and geometric parameters using OpenFOAM - Kaya, Mehmet Numan (Fırat Evirgen, 2025)
Blood flow within biomedical devices and vascular models is characterized by laminar dynamics at relatively low Reynolds numbers, where shear-dependent viscosity governs hemodynamic behavior. This behavior is commonly observed in biomedical applications, such as nozzles, and accurate modeling is essential. In this study, numerical simulations of laminar non-Newtonian blood flow are performed in OpenFOAM using the Bird-Carreau viscosity model to examine the influence of flow conditions and nozzle geometry. The FDA benchmark nozzle is employed as a reference geometry, and the computational setup is validated against available experimental data prior to the parametric study. Five throat Reynolds numbers, $Re = 100, 300, 500, 1000,$ and $1500$, are investigated together with two collector cone angles, $20^\circ$ and $40^\circ$, as well as three throat diameters, $D_t = 3, 4,$ and $5$ mm, to assess geometric effects. The results show that narrower throats and higher Reynolds numbers significantly increase both velocity and shear stress, highlighting the strong sensitivity of hemodynamics to geometric constriction. Pressure drop analysis further reveals that enlarging the throat diameter can substantially reduce losses; for example, at $Re=1000$ and $1500$, increasing the throat from 3 mm to 4 mm lowers the pressure drop by nearly 50%, while a further increase to 5 mm reduces it by about 40%. Overall, the study demonstrates that both geometric variations and flow conditions lead to significant changes in blood flow physics, underscoring their importance in hemodynamic applications.
Keywords: Biological Mathematics; Biyolojik Matematik